Uma (re)aproximação com a áfrica subsaariana: a estratégia da política externa brasileira de 2003 a 2010 - Ahouangan, Agossou Lucien (2017)
The geographical delimitation that will define the international interaction of a country is defined by its foreign policy. The African continent, despite its complex historical relationship with Brazil, has always had a privileged place in Brazilian diplomatic thinking. Cultural and historical ties as well as economic partnership played a very important role in Brazil-Africa relations. But oscillations and setbacks, distance and approximations marked the history of these two parts separated by the Atlantic. In the first decade of the twenty-first century Brazil-Africa relations have been accentuated since the end of the presidential term of Fernando Henrique Cardoso and the beginning of the governments of President Luiz Inácio da Silva. At that moment, Brazil converged towards closer ties with Africa through South-South cooperation and the establishment of new economic partnerships. What we intend to deal with in our dissertation is the understanding of this active foreign policy of President Lula in Africa. Thus the dissertation used commercial data, investments, speech content that were analyzed, projects implemented in two African countries that are Mozambique and Benin. In addition, the dissertation led to the reading of reflections from experts as well as the different stages of implementation of Brazilian foreign policy in Africa. The research led us to the hypothesis that the intensification of the Brazil-Africa relations integrates a double strategy of cooperation for the development of both and international projection of Brazil in its vision of being a global player.